Chronic Suppurative Lung Disease in Children: Definition and Spectrum of Disease - Redding, Gregory J. (Front Pediatr, 2017)
The most common clinical suppurative lung conditions in children are empyema, lung abscess, and bronchiectasis, and to a less often necrotizing pneumonia. Until recently, bronchiectasis was the most common form of persistent suppurative lung disease in children. Protracted bacterial bronchitis is a newly described chronic suppurative condition in children, which is less persistent but more common than bronchiectasis (1). In addition, the term “chronic suppurative lung disease” has been used recently to describe the clinical features of bronchiectasis when the radiographic features needed to make a diagnosis of bronchiectasis are absent. Webster’s New College Dictionary defines suppuration as the process of forming and/or discharging pus. Pus is a body fluid resulting from intense inflammation in response to infection that leads to neutrophil influx and apoptosis, microbial clearance, and often necrosis of nearby tissue. Pus is primarily composed of white blood cell debris.